Effect of Some Factors on Adsorption-desorption of Fulvic Acid on Goethite (α-FeOOH) - , Jaya; Srivastava, P. C.; Agnihotri, A. K.; Ghosh, D. (Indian Forester, 2003)
Using batch technique, the effect of some factors like adsorbate concentration, equilibrium pH, temperature and ionic strength on adsorption-desorption of fulvic acid on goethite (α-FeOOH) was studied. The adsorption isotherms were predominantly of S-type and confirmed to Freundlich equation. The calculated value of adsorption capacity (log K) decreased while slope factor (l/n) increased with the increase in equilibrium pH from 5.0 to 6.0. An increase in temperature from 5° to 20°C increased the adsorption of fulvic acid by many folds but further increase in temperature from 20° to 30°C either decreased the adsorption or did not affect it. An increase in ionic strength decreased the adsorption of fulvic acid. In the case of all factors, the desorption of adsorbed fulvic acid has an inverse relationship with the adsorbed amount. Infra-red spectral evidence indicated that COO and phenolic (OH) moieties of fulvic acid interact with goethite.